Peningkatan Kapasitas Guru dalam Merancang Soal Sumatif Menggunakan Media Digital - Wijayati, Primardiana Hermilia; Ardiyani, Dewi Kartika; Kharis, M (Innovative Journal of Community Engagement, 2025)
Teachers' mastery of competencies in developing summative assessment questions is a crucial aspect in the implementation of the National Curriculum, which is focused on fostering higher-order cognitive skills. This community service activity aims to enhance teachers' competencies in creating summative assessment questions by leveraging the digital platform LearningsApp as the primary medium. The training methods employed include workshops and intensive mentoring sessions involving teachers from various schools. Evaluation results indicate that 75% of teachers feel more comfortable using the digital platform, and 82.36% consider it highly beneficial in developing questions that incorporate higher-order thinking skills (HOTS). This training not only improves the quality of questions and the effectiveness of the question development, distribution, and evaluation processes but also strengthens teachers' professionalism in implementing the National Curriculum. Thus, the application of digital technology in enhancing teachers' competencies is an effective strategy aligned with the needs of 21st-century education and worthy of widespread adoption.